2000
DOI: 10.1093/deafed/5.1.9
|View full text |Cite
|
Sign up to set email alerts
|

How Do Children Who Can't Hear Learn to Read an Alphabetic Script? A Review of the Literature on Reading and Deafness

Abstract: I review the literature on reading and deafness, focusing on the role of three broad factors in acquisition and skilled reading: the method of encoding print; language-specific knowledge (i.e., English); and general language knowledge. I explore the contribution of three communication systems to reading: spoken language, English-based sign, and American Sign Language. Their potential contribution to literacy is mediated by four parameters on which they differ: codability, structural isomorphism, accessibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
0
60

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(165 citation statements)
references
References 72 publications
10
95
0
60
Order By: Relevance
“…This is unsurprising given the close relationship between reading and language in hearing children and the severe vocabulary delays exhibited by most deaf children (see Geers & Moog, 1989;Moores & Sweet, 1990;Kyle & Harris, 2006). Language delay has in fact been described as a hallmark of deafness (Musselman, 2000). In two longitudinal studies of reading development in deaf children from mixed language backgrounds (Kyle & Harris, 2010;, we found that vocabulary and speechreading were the strongest predictors of later reading ability.…”
Section: Deaf Children's Use Of Phonology During Readingmentioning
confidence: 84%
See 1 more Smart Citation
“…This is unsurprising given the close relationship between reading and language in hearing children and the severe vocabulary delays exhibited by most deaf children (see Geers & Moog, 1989;Moores & Sweet, 1990;Kyle & Harris, 2006). Language delay has in fact been described as a hallmark of deafness (Musselman, 2000). In two longitudinal studies of reading development in deaf children from mixed language backgrounds (Kyle & Harris, 2010;, we found that vocabulary and speechreading were the strongest predictors of later reading ability.…”
Section: Deaf Children's Use Of Phonology During Readingmentioning
confidence: 84%
“…Kyle and Harris (2010) reported a strong relationship between phonological awareness and reading in deaf children; however, it is important to note that the direction of this relationship was in fact from reading to phonological awareness. This finding is important as it suggests that deaf children's phonological awareness skills develop as a consequence of learning to read rather than being a precursor of reading ability as is typically found in hearing children (see also Musselman, 2000;Goldin-Meadow & Mayberry, 2001). Moreover, a very recent meta-analysis of the relationship between phonological skills and reading (Mayberry, del Giudice & Lieberman, 2011) concluded there is little consistent evidence of the role of phonology in deaf individuals' reading.…”
Section: Deaf Children's Use Of Phonology During Readingmentioning
confidence: 95%
“…A review of the literature reveals that since the inception of standardized reading testing, children who are deaf have consistently achieved lower scores than their hearing peers (e.g., Allen, 1986; DiFrancesca, 1972;Furth, 1966;Goetzinger & Rousey, 1959;Kroese, et al, 1986;Musselman, 2000;Traxler, 2000;Trybus & Kachmer, 1977;Wrightstone, Aronow, & Moskowitz, 1963). Again, progress from year to year is reported to be slow, and studies report that average yearly improvement is at a rate of 1 to 6 mo (for every 12 mo of education).…”
Section: Discussionmentioning
confidence: 99%
“…The interdependence of spoken language, reading and writing skills is further illustrated in research conducted with deaf children (Lichtenstein, 1998;Musselman, 2000). Numerous studies with children and adolescents who are deaf show that developing reading proficiency has been a long-standing challenge for these people.…”
Section: The Stages Of Reading Proficienciesmentioning
confidence: 99%
See 1 more Smart Citation